HEALING DISCOURSE AND SYMBOLIC COSMOLOGY IN SERAT TETAMBA II: A CRITICAL-HERMENEUTIC DISCOURSE ANALYSIS APPROACH - Junia, Natasya Rachma; Wulandari, Yosi; Agustina, Noor Qomaria (ppjbsip, 2026)
This study re-examines the Serat Tatamba II, a classical Javanese medical text, by integrating Paul Ricœur's philosophical hermeneutics and Critical Discourse Analysis (CDA) to uncover how healing symbols shape cultural meanings, spiritual ideologies, and social authority. While previous research has primarily approached the text through philology and ethnomedicine, this study offers a dual analytical framework to explore the layered symbolic meanings and discursive structures that shape traditional healing practices. The data consists of seventeen symbolic units purposively selected from the translated manuscript. The analysis was conducted through Ricœur's three stages of interpretation, symbolic action, exploration of meaning, and appropriation, combined with elements of CDA that highlight textual meaning, intertextuality, and sociocultural power relations. Findings indicate that healing practices in Serat Tatamba II are structured around three main symbol clusters: purification, energy strengthening, and spiritual protection. Symbols such as turmeric, dugan, black salt, mantras, and ritual movements function not only as healing tools but also as discursive tools affirming cosmological balance, moral discipline, and spiritual authority. This text frames healing as a holistic process that integrates the physical, emotional, and metaphysical.